Human capital and manufacturing activities under environmentally-driven urbanization in the MENA region - Bajja, Salwa; Radoine, Hassan; Celik, Ali; Dakyaga, Francis; Damrah, Sadeq (Frontiers in Environmental Science, 2024)
Middle East and North Africa (MENA) region possesses immense capacity for renewable energy generation. Despite the potential, most countries in the region are yet to fully embrace renewable energy. Non-renewable sources still dominate their energy mix. This study examines the interplay between urbanization, renewable and non-renewable energy consumption, and environmental quality in the six Middle Eastern and North African countries from 1990 to 2021, using the mean group (MG), the mean group dynamic least squares (DOLSMG), the common correlated effect (CCE), augmented mean group (AMG) and the cross-section augmented ARDL (CS-ARDL). Accounting for urbanization, and economic growth, the findings of DOLSMG indicate that while renewable energy and manufacturing activities significantly contribute to environmental quality, urbanization and human capital development significantly contributes to environmental degradation. The CS-ARDL short-term and long run estimation result showed that manufacturing activities significantly contribute to environmental quality, When examined by country, it was found that there is a unidirectional causal relationship from economic growth, manufacturing value added, urbanization, human capital development to dioxide emissions in Saudi Arabia. While there is a unidirectional causality from manufacturing value added to dioxide emissions in Jordan, and a unidirectional causality from urbanization to dioxide emissions in Tunisia.